Інноваційні тренди удосконалення використання оборотних засобів аграрних підприємств - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Векленко, Ю. Г.; Veklenko, Yu. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
У статті проаналізовано основні інноваційні аспекти і шляхи удосконалення використання оборотних активів підприємств. Досліджено теоретичні аспекти щодо визначення економічної категорії "оборотні засоби" аграрного підприємства різними науковцями з погляду ідентичності тотожних дефініцій "оборотні активи" і "оборотний капітал". Авторами удосконалено і уточнено класифікацію оборотних активів за допомогою різних характерних ознакна підставі вивчених теоретичних підходів сформульованих в різних джерелах літератури економічного напряму.Також виявлено напрями ефективності використання оборотних засобів аграрних підприємств. Також наведено складові механізму інноваційної стратегії удосконалення використання оборотних засобів аграрного підприємства. Проведені дослідження показали, що на підвищення ефективності та удосконалення використання оборотних активівздійснюють вплив внутрішні і зовнішні складові інноваційної стратегії підприємств аграрного сектору економіки. The article analyzes the main innovative aspects and ways to improve the use of current assets of enterprises. The theoretical aspects regarding the definition of the economic category "current assets" of an agricultural enterprise by various scientists from the point of view of the identity of the identical definitions "current assets" and "current capital"have been studied. The authors improved and clarified the classification of current assets using various characteristic features based on the studied theoretical approaches formulated in various sources of economic literature. The efficiency of the use of working capital is characterized by the speed of their rotation, turnover. The less they are delayed at individual stages, the faster their cycle is completed. Acceleration of the turnover of these funds is caused by: first, an increase in the volume of production for each monetary unit of the company's current expenses; secondly, the release of part of the funds and, thanks to this, the creation of additional reserves for the expansion of production. Taking into account the mentioned circumstances, when analyzing and planning the company's activities, it is necessary to pay special attention to determining the need for working capital, taking into account the technological and financial conditions formed at the enterprise, as well as sources of their financing, abandoning outdated forms and methods that inhibit the growth of the effective use of working capital means Areas of efficiency in the use of working capital of agricultural enterprises were also revealed. The components of the innovative strategy mechanism for improving the use of working capital of an agricultural enterprise are also given. The conducted studies showed that the internal and external components of the innovative strategy of the enterprises of the agrarian sector of the economy influence the improvement of efficiency and the improvement of the use of current assets. Increasing the efficiency of the use of working capital is ensured by the acceleration of their turnover at all stages of the capital cycle of agricultural production enterprises.
Innovative trends in improving the use of working capital of agricultural enterprises
Keywords: інноваційна стратегія; innovative strategy; оборотні засоби; working capital; оборотний капітал; working capital; аграрне підприємство; agricultural enterprise; використання оборотних засобів; use of working capital